The Effect of Learning Video Education on Knowledge of Breast Milk Dam Prevention in Tri Smester III Pregnant Women in the Working Area of the Dungaliyo Health Center - Narti Hasan; Zuriati Muhamad; Ani Retni (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Breast milk dams generally occur on the 3rd to 5th day after childbirth along with an increase in breast milk production. This condition can be caused by improper breastfeeding techniques, inadequate breastfeeding frequency, improper attachment, and lack of knowledge of breastfeeding by mothers. The purpose of this study is to determine the effect of learning video education on knowledge of breastfeeding dam prevention in third trimester mothers in the working area of the Dungaliyo Health Center. The research method used is quasi-experimental with a pretest–posttest without control group approach. The population in this study is Mrs. Tri Smester III in the working area of the Dungaliyo Health Center with sampling techniques using non-probability sampling techniques with the Total sampling method obtained a sample of 40 respondents. Data analysis was carried out using the Wilcoxon Signed Rank Test. The results of the study showed that before video education, mothers' knowledge was dominated by the sufficient category as many as 26 respondents and the lack category as many as 14 respondents. After the intervention, the majority of mothers had good knowledge as many as 24 respondents, followed by enough knowledge of 13 respondents, and only 3 respondents were still less knowledgeable. The results of the analysis showed an increase in the level of knowledge of respondents after being given video learning education, characterized by a change in the average value of knowledge from 2.35 before the intervention to 1.48 after the intervention, with an average difference of 0.87. The results of the statistical test showed a value of p = 0.000 (p < 0.05), The conclusion of the study was that there was a significant influence of video learning education on the knowledge of breastfeeding dam prevention in third trimester mothers. The results of this research are expected to be a source of information that is easy to understand and access at any time through learning video media.